The Learning Experience Project: Enabling Collaborative Learning with ConferenceXP - Beavers, Jay; Chou, Tim; Hinrichs, Randy; Moffatt, Chris; Pahud, Michel; Eaton, Jason Van (Microsoft Research, 2004)
The Learning Experience Project is an initiative of Microsoft Research’s Learning Sciences and Technology group. The goal of this project is to explore how to make collaborative learning a compelling and rich experience by assuming the availability of emerging and enabling technologies, such as high-bandwidth networks, wireless devices, Tablet PCs, and the advanced features in Microsoft® Windows® XP. The foundation of the Learning Experience Project is the ConferenceXP research platform. ConferenceXP enables universities to build less infrastructure and concentrate on researching and developing collaborative applications that enhance the learning experience in and out of the classroom. By delivering high-quality, low-latency audio and video over broadband connections, as well as providing a flexible common framework, ConferenceXP supports the development of real-time collaboration and video conferencing applications.